The Relationship Between Consumption of Sweet Foods and Beverages and Physical Fitness Levels Among Adolescents - Silvi Puspitasari; Farida Nur Isnaeni (Journal of Physical Education Health and Sport, 2026)
Adolescence is a critical transitional phase marked by significant physical development and changing dietary habits, including an increased preference for sugar-sweetened products. Excessive sugar consumption is theoretically linked to metabolic disturbances and muscle fatigue, which may negatively impact physical fitness. This study aims to investigate the relationship between sugar-sweetened intake and physical fitness levels among adolescents at Batik 1 Surakarta Senior High School. An observational study with a cross-sectional approach was conducted involving 91 adolescent students at Batik 1 Surakarta Senior High School, selected through simple random sampling. Sugar-sweetened intake, encompassing both foods and beverages, was assessed using a FFQ covering the past month. Physical fitness levels were measured using the Harvard Step Test to calculate the Physical Fitness Index (PFI). Data were analyzed using the Chi-Square test to identify significant correlations between variables, with a significance threshold of p < 0.05. The Chi-Square test results showed a p-value = 0,080 with an Odds Ratio (OR) of 2,375 (CI = 0,889-6,344), indicating no statistically significant relationship between the consumption of sweet foods and beverages and physical fitness levels among adolescents at Batik 1 Surakarta Senior High School. However, frequency distribution data revealed an interesting trend; the group of adolescents with infrequent sugar-sweetened intake had a higher proportion of those in the "fit" category (33,3%) compared to the high-intake group (17,4%). This suggests a tendency for decreased physical fitness among individuals who more frequently consume sugar-sweetened products. This study concludes that there is no significant direct relationship between the consumption of sweet foods and beverages and physical fitness levels among adolescents. This suggests the need for further investigation into other contributing factors in future research to better understand the multifactorial complexity of physical fitness.